Pemanfaatan E-Goverment Dalam Menjawab Tantangan Undang Undang No. 14 Tahun 2008 Tentang Keterbukaan Informasi Publik - Ella, Susy (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2010)
Public freedom in obtaining information about government performance is assured by the issuance of Law no. 14 year 2008 on Public Information. With the enactment starting May 1, 2010, each public agency must be able to provide information quickly and timely, low cost, and simple manner. To answer these challenges, the Public Agency can utilize e-government, because policies regarding e-government development is based on information technology will greatly support the Public Agency in providing information to the public